ANALISIS KUALITAS LAYANAN HIGHER EDUCATION PERFORMANCE (HEedPERF) TERHADAP LOYALITAS MAHASISWA DI FAKULTAS 'X' - Ridho Kusmaryadi; Budi Astuti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2017)
Education industry has been the subject of interest in the study, because the modern market today all companies and institutions are required to develop capacity and provide a flexible reaction to survive and develop capabilities advantage in the markets they serve. By understanding the variables of service quality and loyalty of students, not only can help educational organizations in managing its resources optimally as possible, but even more important is to maintain life so as to keep education, as well as building long-term relationships with their students.This study aims to determine the effect of variable HEdPERF (non-academics, academic, reputation, access, and programs offered) the loyalty of the students. The method used in the analysis of Multiple Linear Regression terms to meet Classical Assumption Test to test the hypothesis put forward. Based on the analysis and discussion of the five variables found that HEdPERF only three variables, namely the non-academic, reputation, and at that partially have an influence on student loyalty. While academic and access variables no significant effect on student loyalty. In addition, HEdPERF variables simultaneously affect the loyalty of students amounted to 23.9%, while the remaining 76.1% are other factors beyond the variables HEdPERF. The strong relationship HEdPERF variable loyalty for 52.8% of students can be quite strong. While HEdPERF variables that have most dominant influence on student loyalty program offered is a variable that is by by 8.22%.